Anisotropic band alignment and transport in TMDC junctions with 1T’–2H edge contacts - Shan Jiang; Huan Wang; Xiaojie Liu; Haitao Yin (Results in Physics)
Transition metal dichalcogenides (TMDCs) exhibit remarkable properties and hold a crucial position in the field of materials science. These compounds not only display rich polymorphism but also possess unique electronic structures that endow them with significant anisotropy. By combining density functional theory with non-equilibrium Green’s function, we investigated the anisotropic band alignment in 1T’-MX2/2H-MX2 homojunctions. It was discovered that the zigzag direction has a relatively lower Schottky barrier compared to the armchair direction. We used MoTe2 as an example to construct a field-effect transistor. The lower Schottky barrier in the zigzag direction enables the current in this direction to be consistently higher than that in the armchair direction. However, at Vds = 0.6 V, the on/off ratio is lower along the zigzag direction compared to the armchair orientation.